Fort-Chimo, carrefour de l’est de l’Ungava - Cartier, Yves (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1964)
Fort Chimo is located on the left bank of the Koksoak river 30 miles from Ungava Bay. The Koksoak was first discovered in 1811 by Kohlmeister and Kmoch, Moravian missionaries from Okak on the Labrador Coast. In 1831, two Hudsons Bay traders, Nicol Finlayson and Erland Erlandson, established the original Fort Chimo post on the right bank of the Koksoak river, six miles downstream from the present town. The post had a virtually continuous history of occupance from 1831 until very recently.In 1944, the American army established an air base on the Koksoak river at the present site of the town of Fort Chimo. A great number of the local Eskimos moved away from the old post and congregated about the air base. The Americans abandoned the base in 1948 but most of the Eskimos remained on the site. The new town of Fort Chimo is now located beside the air field and the old post bas been completely abandoned.Fort Chimo had a population of 490 Eskimos and 100-150 whites in 1963. The Eskimos are at grips with serious social and economic problems : poverty, un-employment, alcoholism, etc. However the establishment of a fishing and wood-cutting cooperative in 1961 augures well for the Eskimo community.With the exception of Schefferville, Fort Chimo is the most important centre of eastern Ungava. First a trading post, Fort Chimo now bas an important service and administration junction as well as being a major transportation centre. Fort Chimo can be reached both by air and sea from southern Québec, but most of its supplies arrive by boat.